Edukasi dan Pencegahan Kekerasan terhadap Anak Berbasis Partisipasi Komunitas di Kecamatan Cibinong - Kumala, Destiana; Wasan, Guruh Herman; Harsanto, Molbi Febrio; Arisandi, Rizky; Darmawan, Awan (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2025)
Violence against children in Cibinong District is a critical issue demanding interventions beyond formal legal approaches. This community service aims to establish a sustainable child protection system using Participatory Action Research (PAR). The intervention targeted two primary ecological layers based on Bronfenbrenner’s theory: the family microsystem through Majelis Taklim Khairunnisa and the school mesosystem through SDIT Al Madinah. Through the cycle of mapping, planning, action, and reflection, this program sought to deconstruct social norms legitimizing violence. The results demonstrate three significant achievements: (1) A transformation in parenting styles from authoritarian to positive discipline, alongside the removal of the "disgrace" stigma hindering case reporting; (2) Increased student self-efficacy to speak up against bullying and sexual threats; and (3) The establishment of the Local Child Protection Forum (F-PAL) as a sustainable early warning system institutionalizing community participation. It is concluded that the synergy between family resilience and an inclusive school climate, strengthened by local institutions, is key to effective violence prevention. This model is recommended for replication as an adaptive, community-based child protection policy.